M67. UNDERSTANDING SOCIAL COGNITION IN SCHIZOPHRENIA THROUGH THE LENS OF SCHIZOTYPY. (18th May 2020) - Lee, Sara-Ann; Lim, Keane; Lam, Max; Lee, Jimmy
Abstract: Background: Social cognitive deficits are common, detectable across a wide range of tasks and appear to play a key role in influencing poor functioning in schizophrenia. Despite its importance as a treatment target, the factors that underlie social cognitive deficits in schizophrenia remains elusive. Schizotypy appears to be one such factor that can explain the variability in social cognitive deficits seen in schizophrenia. The study's primary aim was to provide a more comprehensive understanding of social cognitive functioning and its relationship to schizotypy. Methods: 108 patients and 70 healthy controls completed nine tasks across 4 social cognitive domains based on the SCOPE study. In addition, all participants completed the Schizotypal Personality Questionnaire. Clinical symptoms were also rated using the Brief Psychiatric Rating Scale. Results: Theory of Mind, social perception, emotion processing and attribution bias were measured in patients with schizophrenia (n = 108) and healthy controls (n = 70). A social cognition composite score was calculated using principal components analysis. Cluster analysis on the derived factor scores revealed 3 clusters. Multiple univariate ANOVAS with Bonferroni correction were used to examine differences between the 3 clusters on each of the 4 social cognition domain scores, which indicated that higher social cognitive performance was related to lower schizotypy. In addition, results indicated that despite differences in the social cognitive performance among patients in the 3 clusters, they did not differ in clinical outcome measures. Discussion: The primary aim of the study was to address gaps in the current literature by examining the relationship between social cognition and schizotypy. This study built upon past studies which had the tendency to focus on single, discrete domains by comparing the social cognitive performance of patients and controls using an extensive battery of tests, indexing four social cognitive domains. The significant differences on total SPQ score and the SPQ domain scores between the various clusters, coupled with the significant correlations between schizotypy and social cognition, reinforces the utility of schizotypy in refining our understanding of the variation in the degree of social cognitive deficits in schizophrenia. In conclusion, this study substantiates the importance of understanding the relationship between social cognition and schizotypy. This could support and pave the way for the development and implementation of targeted social cognitive interventions catered to the patients' level of deficit.